Bridging the gap between research and frontline youth justice practice. (April 2019) - Ugwudike, Pamela; Morgan, Gemma
Although the Risk, Need, Responsivity model of rehabilitation is rooted in a substantial body of research evidence, several studies of the model's efficacy in youth and adult justice settings within England and Wales have revealed modest outcomes. In this article, we contend that the findings do not necessarily reflect deficits in the model. Rather, a growing corpus of research now indicates that poor practice integrity or inadequate implementation of the model's principles is a key but under-researched factor that undermines the efficacy of interventions based on the model. We also present the findings of a study that explored applications of the model in three Welsh youth justice services and we examine possible means of bridging the gap between research evidence and real-world practice.